Effect of confined Mn oxides on regulating capability of activated coke for persulfate-based oxidation of a sweetener acesulfame - Guoting Li; Haozhe Li; Shude Zhang; Xiao Mi; Yujie Guo; Zhixin Song; Yuhao Liu; Hongwei Pan; Baogui Wang; Yingxu Liu; Weigao Zhao; Tannaz Pak (Water Cycle)
Mn oxides are confined within the porous structure of activated coke (ACO) via impregnation followed by calcination treatment. The Mn-ACO sample calcined at 600 °C (Mn-ACO600) demonstrated superior performance despite containing only a minute atomic ratio of 0.11 % Mn on its surface. This treatment led to a slight increase in the specific surface area and pore volume of ACO, with a significant enhancement in the proportion of micropores, rising from 54.2 % in ACO to 71.8 % in Mn-ACO600. Raman spectroscopy indicated additional defects in Mn-ACO, while XPS analysis confirmed the coexistence of Mn(II), Mn(III), and Mn(IV) oxides. Although ACO adsorption alone was ineffective in removing acesulfame (ACE), Mn-ACO600 achieved a removal rate of 19.0 %. The introduction of peroxydisulfate (PDS) further boosted the degradation of Mn-ACO600, with a Kapp value that was 2.28 times of that of the combined Mn-ACO600 adsorption and PDS oxidation process, indicating a remarkable synergistic effect. To optimize the experimental conditions, a response surface methodology design analysis was conducted, revealing that solution pH and the dosage of Mn-ACO600 were crucial factors. Furthermore, the study confirmed non-radical oxidizing species, such as 1O2 and h+, played a predominant role in the process, with relatively minor contributions from radical oxidizing species.